The Symptom Experience and Management in People with HIV Who Underwent Antiretroviral Therapy During the Covid-19 Pandemic in Bali, Indonesia - Nyoman Agus Jagat Raya; Ni Kadek Ayu Suarningsih (Journal of Nursing Science Update (JNSU), 2022)
Antiretroviral (ARV) therapy does not only provide some benefits but also has side effects that cause symptoms experienced by people with HIV (PWH). Strategies for effective symptom management were needed, especially during the COVID-19 pandemic. The purpose of this study was to explore the symptom experience and management strategies in PWH during the COVID-19 pandemic. A qualitative phenomenology design was used. A cross-sectional with purposive and snowball sampling techniques was used from July to October 2021. Eight participants joined an in-depth interview based on the criteria of the participants, such as people who were infected with HIV, 18 years or older, on ARV therapy, and willing to sign the informed consent. Thematic analysis was used after data saturation was reached. Three themes were found in this study; 1) The symptoms of ARV side effects, which included physical and psychological symptoms that appeared in PWH; 2) The symptom management of ARV side effects, which described the history of hospitalization, pharmacological and non-pharmacological management; 3) The symptom condition during the COVID-19 pandemic. The symptom experience of ARV side effects required strategies to manage the appearance of the symptoms, especially those amid the COVID-19 pandemic. This study could become fundamental evidence to consider in providing nursing care to PWH and supporting the symptom management model among PWH further.